Directions in sign language acquisition - Morgan, Gary, 1968-; Woll, B. (Bencie) (Trends in language acquisition research ;, 2002)
As the first book of its kind, this volume with contributions from many well known scholars brings together some of the most recent original work on sign language acquisition in children learning a variety of different signed languages (i.e., Brazilian Sign Language, American SL, SL of the Netherlands, British SL, SL of Nicaragua, and Italian SL). In addition, the volume addresses methodological and theoretical issues in both sign language research and child language development in general. The book includes both overview chapters addressing matters of general concern in the study of sign lang.